1991
DOI: 10.2134/jeq1991.00472425002000010033x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfometuron Persistence and Movement in Soil and Water in North Dakota

Abstract: Abstract:The lateral movement, soil persistence and aqueous hydrolysis of sulfometuron [2-([{[(4,6-dimethyl-2-pyrimidinyl) from slopes to nontarget areas was minimal and was not detected in the 0-to-30-cm-soil depth, when sampled up to 120 cm downslope from the treated area on 2, 8, or 16% slopes 1 year after treatment. The highest sulfometuron concentration found downslope from the treated area was less than 1 µg kg -1 regardless of the slope. Sulfometuron moved beyond the soil column (70 cm deep) in Fairdale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Imazapyr is rarely detected at 50 cm, but is known to move below 30 cm in several soil types (Rahman et al, 1993). Similarly, the sulfonyl ureas (sulfometuron and metsulfuron) are known to move to 50 cm, but are not reported to move significantly below 70 cm (Walker andWelch, 1989, Lym andSwenson, 1991). In the process of movement through the soil profile, herbicides are acted upon by a variety of degradative and dilution processes.…”
Section: Leaching Through the Soil Profilementioning
confidence: 99%
“…Imazapyr is rarely detected at 50 cm, but is known to move below 30 cm in several soil types (Rahman et al, 1993). Similarly, the sulfonyl ureas (sulfometuron and metsulfuron) are known to move to 50 cm, but are not reported to move significantly below 70 cm (Walker andWelch, 1989, Lym andSwenson, 1991). In the process of movement through the soil profile, herbicides are acted upon by a variety of degradative and dilution processes.…”
Section: Leaching Through the Soil Profilementioning
confidence: 99%
“…Leaching of SM in agricultural and to a lesser extent forest soils has been described. Lym and Swenson (1991) did not detect SM 1.2 m downslope of treated plots with 2, 8, or 16% slopes and concluded that little lateral movement occurred in these North Dakota soils. Following addition of 45.7 cm of water over a period of 48 h in soil leaching experiments, they observed vertical movement in loamy soil columns in excess of 70 cm, but this is an extraordinary amount of water in such a short period of time and probably not representative of any actual field conditions in the USA.…”
Section: Sulfometuron Persistence Summarized From the Literaturementioning
confidence: 92%
“…In acidic environments, hydrolysis is expected to be the dominant degradation pathway of sulfometuron, whereas the herbicide is stable to hydrolysis in neutral or basic environments (Dinelli et al 1997;Montgomery 1997;Trubey et al 1998). The hydrolysis rate increases with increasing soil temperature, low pH, and the presence of adequate soil moisture (Anderson and Dulka 1985;Harvey et al 1985;Lym and Swenson 1991).…”
Section: Reductions In Potato Yield and Economic Return As A Functionmentioning
confidence: 99%
“…Sulfometuron was detected for an average of 429 d in a North Dakota silty-clay loam at pH 6.1 kept at 8 C and 45% field capacity moisture and for only 218 d in the same soil when temperature was increased to 16 C and moisture was kept at 90% field capacity (Lym and Swenson 1991). At temperatures below 10 C, the authors stated that sulfometuron degradation by hydrolysis would have a half-life of several months or more.…”
Section: Reductions In Potato Yield and Economic Return As A Functionmentioning
confidence: 99%
See 1 more Smart Citation